KARAKTERISTIK LIVELIHOOD ASSETS DI KABUPATEN LOMBOK BARAT - Sahar; Slamet Mardiyanto Rahayu; Muhammad Habibullah Aminy; Fathurrahman, Fathurrahman (Nusantara Hasana Journal, 2025)
Kekait is one of the villages included in Gunungsari District, West Lombok Regency. Most of the residents of Kekait Village make their living as farmers with superior natural capital, namely: Oryza sativa (rice), Zea mays (corn), 962 heads of Bos sondaicus (cattle); 632 Capra hircus (goats); 13,080 broiler varieties of Gallus domesticus (broiler chickens); 14,217 heads of Gallus domesticus free-range variety (free-range chickens); 904 Anas domesticus (duck), Mangifera indica (mango), and Arenga pinnata (palm).